Не одна: поэзия / А. Л. Барто ; худож. И. Семенов - Барто Агния Львовна (Мои любимые книжки, 2017)
Экземпляры: ф.13 (20171121) / Инвентарный номер: 54286 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6